Environmental assessment development of anthropogenic objects using comparator identification method - Козуля, Тетяна Володимирівна; Білова, Марія Олексіївна; Козуля, Марія Михайлівна (Eastern-European Journal of Enterprise Technologies, 2015)
The relevance of the paper is in implementing a complex method of natural and industrial objects state assessment in order to predict its impact on the functioning of the natural environment (NE) and making administrative decisions based on solving the problem of ecological and socio-economic and environmental security. The paper provides complex methodological grounds of natural and man-made objects quality assessment introducing the synergetic and entropy-information system analysis component. The paper shows that the socio-environmental aspect of security is to be determined by the compliance of the state of the technological systems with limited impact on the natural components of the research object. Considering "technological system - environment" objects in a large amount of heterogeneous initial information the paper suggests a complex methodological support of quality level assessment of complex systems based on a combination of the principal components and comparator identification methods, which reduces the number of the analyzed factors (the size of the task) without losing the information content. The abilities of this methodical approach in establishing destabilization state system factors are examined which provides the basis for making a balanced management decision, that is self-regulatory mechanisms of state stabilization and introduction of hazards eliminating measures. The paper provides the algorithm of the complex methodological support for environmental assessment of the system object as a sequence of the principal components method and the environmental comparator method which was used to create an analytical sample for analysis. The software is provided as mobile applications for user-oriented gadgets running on Android ranging from the Android 4.1 version and up to Android 4.4 (KitKat). Practical realization of quality assessment methodological support of complex systems with elements of comparator identification is carried out analysing the ecological condition of natural and industrial areas and dangerous industrial Kharkov region objects.